Формування узагальнених паралельних схем алгоритму Флойда-Уоршала - Pohorilyi, S. D.; Maryanovskiy, V. A.; Boiko, Yu. V.; Vitel, D. Yu. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
Floyd-Warshall’s algorithm is formalized using the mathematical tool of modified algorithmic algebras systems. A set of schemes is created step-by-step, and their features and possible problems in using them are considered along with a generalized parallel regular algorithm scheme which takes into account the peculiarities of systems with shared and distributed memory.